Analysing the socio-financial determinants shaping food production in the South African agriculture sector - Thomas Habanabakize; Zandri Dickason-Koekemoer (Cogent Economics & Finance)
The 2023 Sustainable Development Goals (SDGs) encompass a specific objective that is to ‘end hunger, achieve food security, enhance agriculture, and improve nutrition’. The realization of this goal relies heavily on efficient agriculture sector management in developing countries. Consequently, assessment of factors that influence agricultural production is one of the way to solve issues that hinders the attainement of the SDGs. This paper aims to investigate the determinants of food production within the South African agricultural sector. Employing econometric methods like Johansen and Canonical Cointegration, VAR and VECM, this study analyes annual time series data spanning from 1961 to 2022. The analysis indicates that factors such as accessible financing, heightened agricultural sector investment, fertilizer usage, and rural demographic growth positively influence food production; contributing to mitigating food insecurity in South Africa. Conversely, elevated lending rates and inflation pose challenges to South African food production. Thise results indicate the role played by monetary policy to improve food production in South Africa. To bolster food production in South Africa, policymakers shoul focus on enhancing agricultural skills, easing credit conditions to improve financial accessibility, and encouraging active investment from government and private sectors in agricultural activities.